PENGARUH PENAMBAHAN KAPUR TERHADAP KEKUATAN DAN PENGEMBANGAN (SWELLING) PADA TANAH LEMPUNG EKSPANSIF BOJONEGORO - Zaika, Yulvi; ., Suroso; Ranggaesa, Riota Abeng (Jurnal Mahasiswa Jurusan Teknik Sipil, 2017)
Expansive clay soil has a low bearing capacity on condition that the high water level, the nature and development of shrinkage (swelling) were large and high plasticity. One method of stabilization of the soil used in an attempt to improve the quality of the soil is poor, among others, chemical stabilization. Chemical stabilization is done by adding stabilizing agents on the basis of land that will be upgraded. Stabilizing agents used in this study is lime (lime). In this study, the object being observed is, without stabilization of expansive clay and expansive clay with stabilization. Soil stabilized with lime content of 6%, 8%, 9% and 10% of the dry weight of the soil. This study involved testing the physical properties of the analysis granules, Specific Gravity, Atterberg Limit, and compaction, as well as testing the mechanical properties of soil CBR, Swelling, and triaxial. From the results of the test specimen, the native land of the inorganic clay with high plasticity, expands the potential is very high and has a value of current activity. The value of the liquid limit (LL) and plasticity index (PI) decreased with increasing levels of lime, while the value of plastic limit (PL) and the shrinkage limit (SL) increased with increasing lime content. The increase in the value of CBR soaked and unsoaked highest in the percentage of lime addition of 8% and more and more levels of lime are added, the smaller the swelling that occurs. Relationship stress and strain that occurs on lime content of 8%. Keywords : Expansive Clay Soil, Soil Stabilization, Lime, CBR, Swelling, tress and strain